The Komplesitas Sikap Profesional Guru Dalam Pembelajaran Jarak Jauh - Hoerotunnisa Nisa Nisaa (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2021)
This study aims to describe the professional complecity of teachers in daring learning. This reseach is a qualitative. The result of this study showed that; 1) the professional competence of teachers in increasing student interest in learning is mastering teaching materials, managing learning programs, managing classes, assessing achievement, carry out administration, managing teacing and learning interactions, and using learning media/resource. 2) inhibiting factors in daring learning are internal factors and external factors. Internal inhibiting factors is a lack of interest and motivation in students. External inhibiting factors are lack of facilities and infrastructure in online learning, lack of support from parents. Internal supporting factors are the student’s health condition and high enthusiasm form learning. External support factor is support from parents.